Development of Smart Box Learning Media on Earth Layers Material to Improve Student Learning Outcomes - Faradhila Khairunnisa; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2025)
Based on the results of observations conducted by researchers at SD Negeri Jatimulyo, Pati Regency, problems were found in the form of limited learning media and student learning outcomes that were still in the low category on the material of the earth's layers. Based on these problems, it aims to improve the learning outcomes of fifth grade students at SD Negeri Jatimulyo, Pati Regency. This study is based on constructivist theory and Vygotsky's learning theory, emphasizing the importance of peer interaction and cooperative learning in cognitive development. The Smart Box learning media, designed as a real learning tool, combines material summaries, images, experiments, and games to facilitate understanding and engagement among students. The type of research used is R&D research and development using the Brog and Gall model which was modified into 8 stages. The results of the product research showed that the Smart Box learning media was very effective, achieving a validation score of 86% and 87% from media and material experts. The effectiveness of the media using the T test obtained a significant value of 0.00. Student learning outcomes are evidenced by the results of the pretest and posttest. The results of the N-Gain calculation obtained a value of 0.61 with the criteria of "moderate". These findings indicate that the Smart Box learning media is a valuable resource for teachers and can significantly increase students' motivation and understanding in learning about the layers of the earth